2012
DOI: 10.1021/jm201041d
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) Complexes of Salicylic Acid Combining Superoxide Dismutase Mimetic Properties with DNA Binding and Cleaving Capabilities Display Promising Chemotherapeutic Potential with Fast Acting in Vitro Cytotoxicity against Cisplatin Sensitive and Resistant Cancer Cell Lines

Abstract: The complexes [Cu(salH)(2)(H(2)O)] (1), [Cu(dipsH)(2)(H(2)O)] (2), {Cu(3-MeOsal)(H(2)O)(0.75)}(n) (3), [Cu(dipsH)(2)(BZDH)(2)] (4), [Cu(dipsH)(2)(2-MeOHBZDH)(2)]·EtOH (5), [Cu(sal)(phen)] (6), [Cu(dips)(phen)]·H(2)O (7), and [Cu(3-MeOsal)(phen)]·H(2)O (8) (salH(2) = salicylic acid; dipsH(2) = 3,5-diisopropylsalicylic acid; 3-MeOsalH(2) = 3-methoxysalicylic acid; BZDH = benzimidazole; 2-MeOHBZDH = 2 methanolbenzimidazole and phen =1,10-phenanthroline) were prepared and characterized. Structures of 4, 5, and 8 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(66 citation statements)
references
References 45 publications
2
59
0
1
Order By: Relevance
“…As it has been reported previously, the intercalation of planar ligand into the DNA base pairs causes the direct cleavage of DNA without ROS production [81]. The nuclease activity of some intercalating complexes in the absence of reducing agent is attributed to a mechanicaltype of unwinding of the superhelix [78].…”
Section: Dna Interactionmentioning
confidence: 76%
See 1 more Smart Citation
“…As it has been reported previously, the intercalation of planar ligand into the DNA base pairs causes the direct cleavage of DNA without ROS production [81]. The nuclease activity of some intercalating complexes in the absence of reducing agent is attributed to a mechanicaltype of unwinding of the superhelix [78].…”
Section: Dna Interactionmentioning
confidence: 76%
“…It has been observed that in the presence of metal complexes, the covalently closed circular form of plasmid DNA (SC, supercoiled DNA) can be cleaved to nicked circular (relaxed) form (single strand scission) or to linear form (double strand scission) [76][77][78]. The occurrence of nicked and/or linear conformation states of plasmid DNA, monitored by gel electrophoresis, is commonly considered as a result of the DNAmetal complex interaction.…”
Section: Dna Interactionmentioning
confidence: 99%
“…The DNA cleavage properties of the first reported synthetic chemical nuclease, [Cu(phen) 2 ] 2 þ (phen¼1,10-phenanthroline), are dependent on the presence of both exogenous reductant (red; e.g., L-ascorbic acid) and oxidant (e.g., O 2 or H 2 O 2 ) and result from a cascade of redox reactions (i-v) that ultimately lead to the formation of hydroxo (iv and v) and metal-oxo (iv) radical species, which initiate DNA toxicity (Fig. 2) Recently, we have reported that copper(II)-bis-1,10-phen complexes incorporating suitably coordinated dicarboxylate groups (e.g., phthalate or octanedioate) display avid DNA binding and cleaving capability along with powerful in vitro chemotherapeutic activity [65][66][67][68]. These promising findings prompted us to explore this class of compound further.…”
Section: Introductionmentioning
confidence: 99%
“…salicylic acid [30], tetracycline derivatives [31], terpyridine [32], or imidazolidine-2-thione [33]), with remarkable in vitro cytotoxicity towards the human cancer cell lines, none of these dealt with the directed synthesis of mixedligand copper(II) complexes containing flavonoid-inspired co-ligands. In this field of research, we proved in our recent publication [34] that mixed-ligand Cu(II) complexes, containing a bidentate N-donor heterocyclic ligand (phen, bpy or their substituted derivatives), the 2-phenyl-3-hydroxy-4(1H)-quinolinone ligand and nitrate counter anions, of the general composition [Cu(qui)(L)]NO 3 ·xH 2 O, form a solid basis for further projection and evaluation of highly active compounds as potential drugs for the treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%